Increasing Transparency, Mobility And Recognition Of Vocational Studies: The Role Of Accreditation Of Vocational Studies - Hünerli, Selçuk; Yıldırım, Osman (Int Scientific Conference Sgem, 14, Kilment Ohridsky Blvd, Sofia, 1797, Bulgaria, 2009)
Transparency, mobility and recognition in higher education are the aims of the Bologna Declaration. That is why participation in the European Higher Education on Bologna Process provides one of the important stimuli for change in Turkish Universities like many European countries which are currently the members of European Higher Education System. The European credit transfer system for VET (ECVET) in order to allow learners to build on the achievements resulting from their learning pathways when moving between learning systems. ECVET will be based on competences and learning outcomes, taking account of their definition at national or sectoral levels. It will take into account the experience of the ECTS in the field of higher education and the Europass framework. Some principles of a accreditation system for vocational studies are presented, together with consequences for Bologna criteria and procedures. It is concluded that an accreditation system maintains national control and provides an European-wide transparency.
Keywords: VET; ECVET; Transparency; Accreditation; Mobility; Şeffaflık; Akreditasyon; Hareketlilik